2014
DOI: 10.1177/0001699313481226
|View full text |Cite
|
Sign up to set email alerts
|

Religion, friendship networks and home visits of immigrant and native children

Abstract: Using data from a school survey of N¼1190 children at the age of 10 in N¼20590 directed dyads and p* models for network data, we investigate the impact of religion on migrant and native children's friendships and visits at home. Deriving hypotheses from the formation of religious in-groups, our analyses show that having the same or a different religious affiliation as well as regularly attending worship has an impact on having a tie in friendship networks. Visiting alter's home depends more on similarity in wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 36 publications
(44 reference statements)
1
18
0
1
Order By: Relevance
“…De Anstiss and Ziaian (2010) document the importance of close friendship networks for psycho-social support among refugee adolescents, framing them as a barrier to mental health access, as those seeking support are more likely to confide in their intra-ethnic friends than look for professional help. Intra-ethnic friendships have also been blamed for preventing integration (Vedder and Phinney, 2014) and parents have been found to actively encourage friendships with children with similar racial, ethnic and/or religious backgrounds (McPherson et al, 2001;Vincent et al, 2017;Windzio and Wingens, 2014). This study explores the positive aspects of these friendships using different sensory pathways designed to optimise participant expression.…”
Section: Ethnically Homophilous Friendships During Early Adolescencementioning
confidence: 99%
“…De Anstiss and Ziaian (2010) document the importance of close friendship networks for psycho-social support among refugee adolescents, framing them as a barrier to mental health access, as those seeking support are more likely to confide in their intra-ethnic friends than look for professional help. Intra-ethnic friendships have also been blamed for preventing integration (Vedder and Phinney, 2014) and parents have been found to actively encourage friendships with children with similar racial, ethnic and/or religious backgrounds (McPherson et al, 2001;Vincent et al, 2017;Windzio and Wingens, 2014). This study explores the positive aspects of these friendships using different sensory pathways designed to optimise participant expression.…”
Section: Ethnically Homophilous Friendships During Early Adolescencementioning
confidence: 99%
“…People also prefer to associate with similar others (McPherson et al 2001). Religion contains a specific worldview that includes manifold norms and values, so two coreligionists are, on average, more likely to share attitudes, norms, and values than are two individuals who belong to different religious groups (Cheadle and Schwadel 2012; Windzio and Wingens 2014). In line with this argument, research in Europe has found support for homophilous youth friendships: Muslim youths tend to be friends with fellow Muslim peers, and Christian and nonreligious youths are more likely to have Christian or nonreligious friends than Muslim friends (Leszczensky and Pink 2017; Windzio and Wingens 2014).…”
Section: Theorymentioning
confidence: 99%
“…When asking why diversity in general, and religious diversity specifically, could have an impact on social cohesion in these terms, the most obvious reason certainly is homophily. One of the most robust findings in the social sciences is that people tend to have more ties to others who are similar to themselves (McPherson et al 2001), and religious homophily is a well-known manifestation (e.g., Windzio and Wingens 2014;Cook et al 2017). While the tendency to relate to similar others is partly a matter of the opportunity structure (Blau 1977), which has also been called 'baseline homophily ' (McPherson et al 2001, p. 419), empirical network analysis has shown that this tendency is strong also net of the mere availability of contacts.…”
Section: Theory and Past Researchmentioning
confidence: 99%